Springtime Meteorology of Damauli Valley, Nepal: Implications for Climatic Comfort and Environmental Hygiene - Maharjan, Sangeeta (Journal of Institute of Science and Technology, 2015)
Springtime spatial and temporal distributions of temperature and humidity over the Damauli valley have been numerically assessed to examine thermal comfort and environmental hygiene. The study reveals that the near surface temperature over valley may remain at 24, 34 and 27C during the morning, afternoon and in the evening, respectively, and the relative humidity may remain in between 25 to 30% during the spring season. The high temperature and low humidity can significantly degrade environmental hygiene over the valley Journal of Institute of Science and Technology, 2014, 19(2): 24-29